The ACE I allele is associated with higher endurance efficiency of athletes - Pucsok, J.; Dekany, M.; Györe, I. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Genetic markers that are exclusively associated with elite athletes have not yet been identified. Potential candidate genes might be found in the renin-angiotensin system, which plays a key role in the regulation of cardiovascular physiology. We have studied the polymorphisms of the ACE in endurance athletes and in a well-trained control group. Methods The study population comprised 39 endurance athletes. MVVex, VE and VO2max were determined at rest and during the exhaustive treadmill or rowing step test. All subjects were genotyped for ACE I/D polymorphism. Results The frequency of the ACE I allele was significantly higher (p<0.037) in the group showing higher intensity of breathing metabolism than in the group showing lower intensity of breathing metabolism. In the excellent endurance athletes group (elite rowers) the ACE D allele frequency was almost significantly higher than that compared with the unsuccessful athletes (p<0.054). Conclusions The ACE I allele is a genetic marker that might be associated with higher endurance efficiency and an adaptation level of the cardiovascular system. With the examination of the genotype besides the measurement of acute physical activity it is worth to taking into consideration the long-term efficiency of endurance performance also, for the purpose of understanding the more accurate relationship.